2017
DOI: 10.21037/cdt.2017.10.14
|View full text |Cite
|
Sign up to set email alerts
|

May-Thurner: diagnosis and endovascular management

Abstract: Common left iliac vein compression, otherwise known as May-Thurner (MT), is an anatomical risk factor for lower extremity deep vein thrombosis (DVT). MT refers to chronic compression of the left iliac vein against the lumbar spine by the overlying right common iliac artery. The compression may be asymptomatic. The syndrome is a clinical spectrum of physical findings and history plus the lesion. It is characterized by the varying degrees of venous hypertension. This can be non-thrombotic, combined with acute DV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(114 citation statements)
references
References 22 publications
0
95
0
9
Order By: Relevance
“…Symptomatic ILVC can present with a variety of symptoms most commonly lower extremity swelling, claudication, hyperpigmentation, varicose veins and/or venous ulceration. Patients may report tighter shoes in the affected leg at the end of the day with more fatigue and swelling 5. The quality of life (QOL) in patients with ILVC is reduced, particularly in those who develop DVT with post-thrombotic syndrome (PTS).…”
Section: Epidemiology Symptoms and Quality Of Life Of Patients With mentioning
confidence: 99%
“…Symptomatic ILVC can present with a variety of symptoms most commonly lower extremity swelling, claudication, hyperpigmentation, varicose veins and/or venous ulceration. Patients may report tighter shoes in the affected leg at the end of the day with more fatigue and swelling 5. The quality of life (QOL) in patients with ILVC is reduced, particularly in those who develop DVT with post-thrombotic syndrome (PTS).…”
Section: Epidemiology Symptoms and Quality Of Life Of Patients With mentioning
confidence: 99%
“…However, several factors can limit the technical success of imaging of the inferior vena cava and iliac veins with ultrasound. 8 Axial imaging such as computed tomography or magnetic resonance imaging can be used to demonstrate narrowing of the iliac vein and to identify other potential causes of clinical symptoms. However, timing of these studies for optimal opacification of the venous system can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Computed tomography venogram is the optimal noninvasive imaging modality for diagnosis but can also be used for posttreatment monitoring. 11,12 Choi et al reported 92.9% predictive accuracy of CT venogram for identifying venous occlusion within 6 months of catheter-directed thrombolysis. 11 IVUS has the added advantage of correlating age of thrombus, identifying collateral formation and measuring intravenous pressures in addition to ensuring accurate guidewire and stent placement during endovascular treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11 IVUS has the added advantage of correlating age of thrombus, identifying collateral formation and measuring intravenous pressures in addition to ensuring accurate guidewire and stent placement during endovascular treatment. 10,12,13 Treatment options include endovascular or open surgical procedures. Anticoagulation with open thrombectomy has been proven ineffective with a high rate of recurrence.…”
Section: Discussionmentioning
confidence: 99%